PENILAIAN PENGUNJUNG PADA FASILITAS OBJEK WISATA AIR TERJUN GURUH GEMURAI DI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Satria Safa; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In a study using this descriptive quantitative research method, there is a purpose to find out how the assessment of visitors at the attraction facility waterfall thunder gemurai in kuantan district singingi riau province. Besides this research also try to know the expectation of visitor at facility of wisata wisata waterfall thunder gemurai and what effort pengelolah (government) in overcoming problem existing in wisata waterfall thunder gemurai district kuantan singingi riau province.Based on the results of research that has been done there are results that show the assessment of visitors at the facility attractions waterfall thunder gemurai in kuantan regency singingi province riau quite good overall. It is based on the measurement scale used. In addition, visitors have expectations of all the facilities, cleanliness of the locker room, repair and addition of changing rooms and toilets and repairing stairs. And the efforts of the parties to overcome the existing problem is to perform maintenance, repair and management at the object of waterfall thunder gemurai quake district singingi riau province. Keywords: appraisal, facilities, visitors, attractions